COMPENSATION FACTORS, HUMAN RESOURCE DEVELOPMENT POLICIES AND LEADERSHIP STYLES THAT AFFECT EMPLOYEE PERFORMANCE - Edward Alezandro Lbn. Raja, Mr; Rozaini; Davidly Manullang; Putra Raja Tunggal Hasugian; Rasikun (LPPM STIE EKA PRASETYA, 2024)
Abstract. In a company, the goal of all organizations is how to achieve the company's goals, namely achieving maximum profit, which is the focus of all workers and company owners.To achieve the company's goals, various policies will be carried out in optimizing existing business activities in the company so as to achieve high productivity.Providing attractive compensation for employees is the company's effort to give confidence to employees so that it will influence employee behavior to work even harder.The company must be committed to improving the quality of employees in order to create high performance for the company.Improving the quality of employees can be done through employee quality development policies through increasing employee education and experience.The relationship between superiors and subordinates will be harmonious if the relationship can be harmonious between superiors and subordinates where in this company it is called the term manager and employee.Managers as company leaders must be able to manage the company's potential well through empowering employees and empowering other resources such as capital, buildings, land in the company.In carrying out their duties, each manager has a different leadership style so that the manager's leadership style will be able to influence changes in employee behavior in a good direction.Employees as executors of work at the lower level will provide good performance with the attention given by the company through various policies in the company.